Experimental and Finite Element Study of Rollover Protection Structure for a 22-Seat Man Hauler Superstructure Vehicle - Muchamad Gozali; Djoko Wahyu Karmiadji; Wina Libyawati; Budi Haryanto; Muhamad Masrur; Arief Setyawan; Wahyu Sulistiyo; Makmuri Nuramin; Anwar Anwar; Budi Susilo (Universitas Muhammadiyah Magelang, 2024)
The application of man hauler which classified as heavy-duty vehicle and operated on the upper ground mining, requires high safety measurement as arrange in the UN-ECE No. 66. The safety measure demands vehicles to undergo both structural testing and analysis. The investigation of structural testing for heavy-duty vehicles has been developed to the rollover testing that used tilting platform, to see the deformation impact toward the residual space and foresight opportunities for further development on the vehicle structure or warning system. Rollover testing is costly and time consuming, so new or developed vehicle structure needs finite element model analysis, to predict the deformation level due to rollover incident. Both testing have the same goal which is to confirm the vehicle structure able to protect the passenger compartment. Therefore, this study aims to present a guidance to test a complete set of 22-seat man hauler vehicle with stress distribution analysis, quasi-static loading test of body section, and tilting platform. The results of the stress distribution test are that the load is concentrated on the element number 148 in the rear UNP 100 profile. The results of the quasi-static loading test are that the maximum stress that occurs is 33 % b the allowable stress. The simulation result under this condition shows that the maximum deflection value occurred in the side frame structure is 167.9 mm. The largest deformation due to rolling test occurred at point E has value of 27 mm located on the right side that experienced impact on the floor during the test. The overall testing and analysis are able to verify and confirm the vehicle structural strength, that the vehicle able to withstand the rollover impact and to protect the passengers.